Evaluation of a gene-by-gene approach for prospective whole-genome sequencing-based surveillance of multidrug resistant Mycobacterium tuberculosis - Macedo, Rita (2020)
Supplementary data to this article can be found online at https:// doi.org/10.1016/j.tube.2019.02.006.